Fully printed organic solar modules with bottom and top silver nanowire electrodes - Tam, Kai Cheong; Kubis, Peter; Maisch, Philipp; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2021)
One of the advantages of organic photovoltaics (OPV) over other contemporary technologies is its relative ease of processing. There are, however, very few works that have realized fully printed devices, including the bottom electrode, let alone with a scalable process in a reasonable device size (>1 cm(2)). In this work, design steps and optimization processes towards fully printed OPV modules with scalable processes are demonstrated for the first time. An overview on issues related to upscaling with printed electrodes is first provided. The various issues are then addressed by a rational design process supported by measurements and calculations. Finally, a set of fully printed OPV modules are fabricated using these optimized parameters that have over 3.5-cm(2) active area with 5% efficiency. For the first time, this work has also demonstrated the process compatibility of fully printed device structures with non-fullerene acceptor systems, which enables more design opportunities for the current generation of high-performance OPV materials.
CRIS-Team WoS Importer:2021-12-31